Pluralisme Berbasis Pendidikan Agama Guna Pencegahan Radikalisme Agama - Abdul Rohman (Al-Ulum, 2016)
Radicalism has recently become a phenomenon. Violences in some areas of Indonesia is a proof. These violences are caused by the conflict that is be partly due to a plurality. These problems have to be overcome in order to shape the unity of the nation. This study will discuss the role of schools in developing the diversity of students in response to the religious plurality in society, which will be focused on how the curriculum is constructed, teaching-learning is done, as well as how the teacher and student’s understanding on religious pluralism is, as a result of the education process. With a qualitative research, a case study in SMA Madania Bogor West Java, this study shows that school with a pluralistic based religious education, fits for internalizing the values of pluralism, in turn forming tolerances and inclusiveness.